MORPHOMETRY AND MORPHOTECTONIC OF CIANTEN AND CISAAT WATERSHED ON QUATERNARY VOLCANIC TERRAIN, GARUT, WEST JAVA - Sipahutar, Sumahang R.; Sukiyah, Emi; Sulaksana, Nana (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
The research area is located in the Baluburlimbangan, Garut regency, West Java Province.Geographically, the research area is located at 107° 52' 23.32